Land and violence in the south sierra of Oaxaca, México (2013)
The states of Oaxaca, Chiapas, Veracruz and Guerrero have a great presence of rural communities with elevated indicators of poverty, illiteracy and an absenceof the most basic services. Diverse political parties, civil organizations, lawyers, priests and regional bosses take advantage of this situation in order to promote socialtensions that become divisions between neighboring towns, due to land possession, the use of water and natural resources.In this text we present a general landscape of the dificult situation of the agrarian issue in Oaxaca, of the people’s manifestations regarding agrarian conlicts, their demands, tactics, and the ways in which federal and state institutions have attempted to solve them. In the same way, we present the testimony of a case occurredon May of 2002, where under the pretext of an ancestral dispute between two towns regarding the indeinition of their territorial boundaries, forest exploitation and that of other natural resources, 26 natives were massacred by a paramilitary group, a crime that remains unpunished to this date. Government authorities promote permanentoblivion, while the 28 widows and 89 orphans continue to wait for the support offered, and for the material and intellectual authors of the crime to be punished accordingto the law.